2021
DOI: 10.1186/s12889-021-10577-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with elevated low-density lipoprotein cholesterol levels among hill tribe people aged 30 years and over in Thailand: a cross-sectional study

Abstract: Background Low-density lipoprotein cholesterol (LDL-C) is one of the most important types of cholesterol and has an impact on health. Certain lifestyle and dietary habits in different populations may leads to increased levels of LDL-C, particularly among those with poor education and economic statuses, such as hill tribe people in Thailand. This study aimed to estimate the prevalence of and determine the factors associated with high LDL-C levels among hill tribe people in northern Thailand. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…A previous study showed that people who obtained incorrect knowledge toward diabetes did so due to language differences ( 38 ). It is consistent with the study which showed one group of people did not have sufficient knowledge to take care of their own health due to lack of communication skills, which prevented them from accessing healthcare information and managing their diabetes ( 35 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A previous study showed that people who obtained incorrect knowledge toward diabetes did so due to language differences ( 38 ). It is consistent with the study which showed one group of people did not have sufficient knowledge to take care of their own health due to lack of communication skills, which prevented them from accessing healthcare information and managing their diabetes ( 35 ).…”
Section: Discussionsupporting
confidence: 88%
“…They also pointed out that smoking is a risk factor for cardiovascular disease ( 53 ). We showed that the Karen community had lower levels of HbA1c compared with those of the Indigenous group, which is similar to a study showing that racial/ethnic differences can result in higher triglyceride levels ( 35 ). Studies have shown that certain tribes from Lua and Hmong communities carried a significantly higher risk of coronary artery disease compared with that of other ethnic groups, which suggests that differences in racial/ethnic backgrounds can affect triglyceride levels ( 33 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While smoking behavior is commonly found among Akha men and women, Lisu women and Karen women do not smoke [ 27 ]. Lisu and Akha cooking practices are similar to Chinese cooking practices, which involve oil, while Karen people use less oil in their daily cooking practice [ 28 , 29 ]. Certain health-related behaviors and cooking practices can influence the development of prediabetes in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…As a major trigger of mortality worldwide, the epidemic of cardiovascular diseases (CVDs) is predicted to spread rapidly in developing and developed countries along with the high prevalence of risk factors, including hypertension, diabetes, and obesity (1). In 2016, CVDs caused ∼17.9 million deaths globally (2). The mortality of CVDs worldwide is estimated to reach nearly 23.6 million in 2030 (3).…”
Section: Introductionmentioning
confidence: 99%